GEOLOGICAL EXPLORATION POTENTIALS AND GEOCHEMICAL STUDY ON ROCKS AND ORES IN SHAQUANZI COPPER AND COPPER-IRON DEPOSITS, EAST XINJIANG - Fang W.X.; Gao Z.Q.; Jia R.X.; Liu Z.T.; Li F.S.; Xu G.D. (My University, 2006)
Rock associations of andesites and diorite in Shaquanzi copper-iron deposits in East Tianshan Mountain in Xinjiang, China, are attributed to cal-alkaline, at close range of alkaline, volcanic rock series. The concentrations of SiO2 in andesites are from 49.2% to 59.97%. Ranges of Na2O contents in andesites are 2.19% to 5.1% while K2O from 0.61% to 3.2%, with the concentrations of Na2O and K2O from 5.32% to 7.03%, and ratios of Na2O/K2O from 1.07 to 8.36. However, contents of Al2O3 more than 16% in most andesite samples are similar to those in high-Al basalt. Furthermore, results of their geochemical properties showing that andesites and diorites are characterized by obvious positive anomalies of Rb, Th-U-K, La-Ce, Pb and P, obvious enrichment of LREE and LILE, noticeable negative anomaly of Ta-Nb and Sr, and moderate negative anomaly of Eu and Ti. Therefore, it can be inferred that the andesites and diorites related to copper and iron mineralization in the study area would possibly yield in the background of continental margin arc based on their observed geochemical natures, which is the most favorable geological background for skarn and porphyry Cu-Fe deposits. Exploration orientation can be focused on blinded skarn and porphyry Cu-Fe deposits at the depth with the high potential in the Shaquanzi area.
Keywords: ACTIVE CONTINENTAL MARGIN; ANDESITE; DIORITE PORPHYRY; SHAQUANZI CU-FE DEPOSITS; SKARN-PORPHYRY CU-FE DEPOSITS